Design, development and in vitro–in vivo study of tramadol–paracetamol inlay tablets. (1st February 2014) - Kotta, Sabna; Bijumol, C.; Anitha, Y.; Dileep, K. J.; Valsala, Kumari
Abstract: The objective of this work is to formulate, optimize and evaluate in-lay tablets of tramadol–paracetamol. This study investigated the effect of hydrophobic, plastic and hydrophilic types of polymers and their content level on release profile of a highly water-soluble drug tramadol hydrochloride. A 3 2 full factorial design was employed for the optimization of the sustained release (SR) formula of tramadol hydrochloride using ethyl cellulose, eudragit and carbopol. CP9 (66% carbopol and compression load of 6 ton) with a percentage drug release of 89.03 after 12 hours were found to be most comparable to the marketed product in terms of similarity factor and most appropriately fits to zero-order kinetics. Hence, it was selected for in vivo study. Statistical analysis of in vivo studies showed that the plasma drug level after oral administration from the prepared formulation is almost comparable to the marketed product ( p < 0.05). Pharmacokinetic analysis of the optimized tablet formulation CP9 were done to find out relevant pharmacokinetic parameters. The results showed that Cmax, tmax, AUC, AUMC, MRT were comparable to the marketed preparation. The formulation exhibited a good in vitro–in vivo correlation ( r 2 = 0.971).